A study on the effectiveness of Manila City library main branch to support the alternative learning system (ALS) learners - Baroma, Claudine B. (School of Library and Information Studies, University of the Philippines Diliman, 2016)
In a recent study conducted by the Philippine Statistics Authority (PSA), the number of out-of-school youth (OSY) in the country is nearly four million or 1 in every 10 Filipino youth. The NCR placed as 2nd region that has a high number of OSY's. In order to solve the issue of having numbers of OSYs in the country, one of the national strategies of the Philippine government in the Alternative Learning System (ALS). Since libraries are considered as one of the venues where the ALS program can take place, public libraries are in good position to serve and provide the information needs of ALS learners. They play an essential role in the society for everyone.